Lesson From Pedagogical Translation: Translation as a Learning Strategy in English Education Program - Imran, Muhammad Chairil; Jubhari, Yuriatson; Sasabone, Luana; Kaharto; Marzuki, Mutmainnah; Bashar, Khaliq (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
This study examined the function of translation as a pedagogical instrument in English language education programs, highlighting its possible advantages and drawbacks as a learning technique. This study used a qualitative approach to gain data through documentation and interviews with EFL learners at the university. The findings indicate that translation can significantly aid language acquisition when employed in conjunction with communicative approaches, particularly by improving vocabulary acquisition, grammatical comprehension, and cultural awareness among learners. Equilibrating translation with alternative interactive language learning methods is crucial to prevent overreliance on the first language (L1), which could impede natural language processing in the target language (L2).  It can be concluded that Translation, when combined with communicative methods, greatly supports language learning by boosting vocabulary, grammar, and cultural understanding.